Cotton Cultivation Practices in South-Western Part of Punjab - Sharma, Karamjit; Kumar, Vivek; Singh, Gurmail (Indian Journal of Extension Education, 2024)
The study was conducted for three consecutive years (2018/19-2020/21) to investigate the adoption status of cotton crop production practices in Sri Muktsar Sahib district in south-western Punjab. Data pooled for three years showed that the majority of farmers (67.8%) ensured crop sowing at the recommended time, while 32.8 per cent delayed cotton sowing due to the non-availability of canal water for timely pre-sowing irrigation. Concerning nutrition management, 18.5, 45.5 and 33.5 per cent of farmers applied recommended doses of N, P, and K fertilizers, respectively, and 89.5 per cent of farmers applied two or more sprays of potassium nitrate (KNO3). For the management of insect pests, during 2018-19, ~52.9 per cent of farmers had to apply 5-6 sprays, while during the next two years, ~55.4 and 81.5 per cent of farmers applied 3-4 insecticide sprays. The average seed cotton yield during 1st year of study (2018-19) was 15.6 q ha-1 which was increased to 22.6 q ha-1 during 2019-20 and 23.1 q ha-1 during 2020-21. This study reiterates that there is a need to update the farmers regarding knowledge of improved cotton cultivation techniques for efficient weed, nutrition, water, and insect-pest management in cotton cultivation in Punjab.
Keywords: Cotton cultivation practices; Cotton productivity; Extent of adoption; South-western Punjab